2021
DOI: 10.1002/cti2.1348
|View full text |Cite
|
Sign up to set email alerts
|

TIGIT blockade enhances NK cell activity against autologous HIV‐1‐infected CD4+ T cells

Abstract: Objectives. During chronic human immunodeficiency virus (HIV)-1 infection, inhibitory molecules upregulated on lymphocytes contribute to effector cell dysfunction and immune exhaustion. People living with HIV (PLWH) are at greater risk for age-related morbidities, an issue magnified by human cytomegalovirus (CMV) coinfection. As CMV infection modifies natural killer (NK) cell properties and NK cells contribute to protection against HIV-1 infection, we considered the role of T-cell immunoreceptor with immunoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 73 publications
(176 reference statements)
2
13
0
Order By: Relevance
“…Similarly, CTLA-4 blocking agents also augment HIV-1 antibody responses, either alone or in combination with OX40 agonistic antibodies [74]. PD1 and TIGIT blockade have also been shown to enhance NK cell function [75,76]. Finally, the combination of different ICB (i.e., CTLA4, LAG-3, and TIGIT) might also be beneficial in improving anti-HIV immune response [77], although potential adverse effects of such a combination cannot be ruled out.…”
Section: How Can the Vaccinal Effect Be Improved?mentioning
confidence: 99%
“…Similarly, CTLA-4 blocking agents also augment HIV-1 antibody responses, either alone or in combination with OX40 agonistic antibodies [74]. PD1 and TIGIT blockade have also been shown to enhance NK cell function [75,76]. Finally, the combination of different ICB (i.e., CTLA4, LAG-3, and TIGIT) might also be beneficial in improving anti-HIV immune response [77], although potential adverse effects of such a combination cannot be ruled out.…”
Section: How Can the Vaccinal Effect Be Improved?mentioning
confidence: 99%
“…Expression of TIGIT, an inhibitory receptor and classical immune checkpoint, is elevated in chronic infectious diseases or tumors and related to NK cell dysfunction ( 34 , 35 ). Zhang et al.…”
Section: Nk Cell Dysfunction During Hiv Infectionmentioning
confidence: 99%
“…Immunoreceptor Tyrosine-Based Inhibition Motif (ITIM) Domains (TIGIT) and DNAM-1(CD226) Expression of TIGIT, an inhibitory receptor and classical immune checkpoint, is elevated in chronic infectious diseases or tumors and related to NK cell dysfunction (34,35). Zhang et al found that an increase in the number of NK cells expressing TIGIT leads to higher HIV load, and TIGIT pos NK cells exhibit less-effective killing than TIGIT neg NK cells in HIV-infected individuals (36).…”
Section: T-cell Immunoreceptor With Ig Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, CD155 expression by T cells combined with NKG2D expression on NK cells has been described to increase cytotoxic capacities to eliminate HIV-infected cells in vitro [70]. On the other hand, blockade of the inhibitory checkpoint inhibitory receptor TIGIT on NK cells, which is the ligand of CD155, increases NK cell activity against HIV-1 infected CD4þ T cells in PWH in vitro [71].…”
Section: Potential Implications For Novel Hiv-1 Cure Strategiesmentioning
confidence: 99%